(untitled) (Heródoto: Revista do Grupo de Estudos e Pesquisas sobre a Antiguidade Clássica e suas Conexões Afro-asiáticas, 2018)
The object of this article is to draw attention to a dimension of the reception of the memories around the poet Sappho and the Island of Lesbos: that represented by the political uses made by militants and feminists groups and, above all, lesbian-feminist groups. Through the presentation and commentary of two examples currently found in Brazil, that I intend to draw attention to the relevance of the analysis of this type of reception.